C2‐linked alkynyl poly‐ethylene glycol(PEG) adenosine conjugates as water‐soluble adenosine receptor agonists. (22nd August 2022) - Ferguson, Lindsay; Madieh, Nasrin Shokrzadeh; Vaideanu, Alexandra; Schatzlein, Andreas; Festa, Joseph; Singh, Harprit; Wells, Geoffrey; Bhakta, Sanjib; Brucoli, Federico
Abstract: A series of 12 novel polyethylene‐glycol(PEG)‐alkynyl C2‐adenosine(ADN) conjugates were synthesized using a robust Sonogashira coupling protocol and characterized by NMR spectroscopy and mass spectrometry analysis. The ADN‐PEG conjugates showed null to moderate toxicity in murine macrophages and 12c was active against Mycobacterium aurum growth (MIC = 62.5 mg/L). The conjugates were not active against Mycobacterium bovis BCG. Conjugates 10b and 11b exhibited high water solubility with solubility values of 1.22 and 1.18 mg/ml, respectively, in phosphate buffer solutions at pH 6.8. Further, 10b and 11b induced a significant increase in cAMP accumulation in RAW264.7 cells comparable with that induced by adenosine. Analogues 10c, 11c and 12c were docked to the A1, A2A, A2B and A3 adenosine receptors (ARs) using crystal‐structures and homology models. ADN‐PEG‐conjugates bearing chains with up to five ethyleneoxy units could be well accommodated within the binding sites of A1, A2A and A3 ARs. Docking studies showed that compound 10b and 11b were the best A2A receptor binders of the series, whereas 12c was the best binder for A1 AR. In summary, introduction of hydrophilic PEG substituents at the C2 of adenine ring significantly improved water solubility and did not affect AR binding properties of the ADN‐PEG conjugates. Abstract : Non‐cytotoxic C2‐linked alkynyl oligo ethylene glycol adenosine conjugates are highly water soluble and stimulate adenosine receptor activity.